Independent coding of reward magnitude and valence in the human brain. - Yeung, N; Sanfey, A (2004)
Previous research has shown that two components of the event-related brain potential, the P300 and feedback negativity, are sensitive to information about rewards and penalties. The present study investigated the properties of these components in a simple gambling game that required participants to choose between cards that were unpredictably associated with monetary gains and losses of variable magnitude. The aim was to determine the sensitivity of each component to two critical features of reward stimuli: magnitude (small or large) and valence (win or loss). A double dissociation was observed, with the P300 sensitive to reward magnitude but insensitive to reward valence and the feedback negativity showing the opposite pattern, suggesting that these two fundamental features of rewarding stimuli are evaluated rapidly and separately in the human brain. Subsequent analyses provided additional evidence of functional dissociations between the feedback negativity and P300. First, the P300 (but not the feedback negativity) showed sensitivity to the reward value of alternative, nonselected stimuli. Second, individual differences in the amplitude of the feedback negativity correlated with individual differences in risk-taking behavior observed after monetary losses, whereas individual differences in P300 amplitude were related to behavioral adjustments observed in response to alternative, unchosen outcomes.